Ernest J. St. Jacques passport - St. Jacques, Ernest J., 1890-
Special passport issued to St. Jacques as a member of the Inter-Allied Commission. Issued for travel in Europe following World War I by the American ambassador in Paris, France.
Member of Inter-Allied Commission.
Collection material in English.
Keywords: Inter-Allied Commission; World War, 1914-1918.; Europe -- Description and travel